Emotion priming in Malay-Arabic bilinguals - Jaffer, Usman (Forest Research and Management Institute ICAS, 2022)
It is argued that even though emotion is experienced differently in the bilingual’s the first (L1) and second (L2) language as a survival mechanism emotion has to be processed at the onset of word presentation. Aim: The aim of this study was to investigate emotion evaluation and processing in visual recognition of words across the languages of Malay-Arabic bilinguals. Method: A total of 68 participants with Malay as L1 and Arabic as L2, ranging from 19–24 years of age (M= 20.79 ± 1.51 years) were recruited. The priming paradigm was used in four language conditions L1–L1, L2–L2, L2–L1, and L1–L2. For each of the four language conditions, these reflect the factors, prime exposure (masked/overt), prime type (control, emotion), and target valence (neutral, positive, negative) Results: In L1–L1, there is no evidence of emotion priming and emotion priming effects. Moreover, L1–L1 and L2–L2 were near equivalent in a lack of any emotion priming, except for L2–L2 neutral targets under overt conditions, when there was evidence of emotion priming. In L2–L1, the main effect for prime exposure was not significant, except possibly in emotion primes following a negative target. Finally, negative emotion priming was found when targets were neutral in both the masked and the overt conditions. No emotion priming was found for positive and negative targets. Conclusion: This study was interested in the valence processing in Malay-Arabic bilinguals. It found that emotions were processed when word were incongruent in L2. Positive emotion processing was also observed at the subliminal level in L1. While L1 emotional primes inhibited processing of neutral targets, L2 emotion primes facilitated L2 neutral targets. Surprisingly no emotional priming was evident for negative valence items. Further study is warranted in these effects with a larger sample.